(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The purpose of the study is to find out the effects of own body exercises and plyometric training on coordination of badminton players. The study was formulated as a true random group design consisting of a pre-test and post test. The subjects (N=60) were randomly assigned to three equal groups of twenty. The selected subjects were divided into three groups randomly. Experimental Group I was considered as own body weight exercises group, experimental group II was considered as plyometric exercises group and control group was not involved in any special treatment. Pre test was conducted for experimental Groups I and II and the control group on coordination. Experimental groups underwent the respective training for 12 weeks. Immediately after the completion of 12 weeks training, all the subjects were measured of their post test scores on the selected criterion variables. The difference between the initial and final scores was considered the effect of respective treatments. To find out statistical significance of the results obtained, the data were subjected to statistical treatment using ANCOVA. In all cases 0.05 level was fixed to test the significance of the study.